Failure Analysis of Duplex Stainless Steel for Heat Exchanger Tubes with Seawater Cooling Medium - Husaini Ardy; Thomas Albatros; Afriyanti Sumboja (Metals, 2023)
The present paper describes a study case of the failure investigation of duplex stainless steel (UNS S31803) on the tube and tube sheet sections of BEM TEMA-type shell and tube heat exchanger with seawater as the cooling medium. The heat exchanger’s shell design pressure was 22.6 MPa at 422 K, and the tube design pressure was 1 MPa at 339 K. Although UNS S31803 offers high strength, high resistance to chloride-induced SCC, and high resistance to pitting attack in chloride environments, the heat exchanger in this study experienced some material degradation after 28 months of use; 102 out of 270 tubes failed, 26 tubes leaked and were plugged on both sides, and scale plugged 76 tubes. The examination in this study case revealed the formation of white-colored biofilm inside the tubes; XRD examination revealed that the film contained CaCO3. Using microstructural examination on the inner surface of the tube, the austenite grains were shown to have been preferentially attacked; this phenomenon is typical in duplex stainless steel which fails due to crevice corrosion. According to the examination result, the failure in this case was caused by crevice corrosion between the substrate and surface deposits that was enhanced by microbiological-induced corrosion (MIC). Recommendations to avoid similar failures are also suggested in this paper.